Comparative Study in the Comuna Santa Clara de San Millán, Quito - Pedernales Earthquake April 2016 - Ponce, Jorge; Fernandez I.; Bernal F.; Labrada Y. (My University, 2023)
The Comuna Santa Clara de San Millán is located in the city of Quito, which is a high seismic risk area. On April 16, 2016 an earthquake in Pedernales, Ecuador caused 683 fatalities and substantial material damage [1]. The purpose of the study was to compare the elements of seismic vulnerability manifested in the Comuna Santa Clara de San Millan with those recorded in the Pedernales earthquake. To achieve this, the work evaluates the seismic vulnerability of Comuna Santa Clara de San Millán using qualitative methods, identifies factors in common with the Pedernales earthquake and contrasts the results obtained. The analysis of the data allowed finding typical elements in both sites, such as the construction typology of reinforced concrete frame with unreinforced walls, irregularity in elevation, flat slab with flat beams, and flexible first floor or weak story; it was also identified that 91.7% of the houses reviewed are evaluated as highly vulnerable. The conclusions show the similarity of the structural problems in both places, so similar results could be expected in the event of an earthquake with similar characteristics to the one in Pedernales. This shows the need to continue the seismic vulnerability studies, now using quantitative methods, and to carry out structural reinforcement work in the buildings that require it in the Santa Clara de San Millán Commune. © 2023 IEEE.
Keywords: Cultural representation; Decolonial design; Inclusive gaming; Narrative challenge; Video games